2018
DOI: 10.1111/dmcn.13751
|View full text |Cite
|
Sign up to set email alerts
|

The Eating and Drinking Ability Classification System: concurrent validity and reliability in children with cerebral palsy

Abstract: Aim As there is little evidence for concurrent validity of the Eating and Drinking Ability Classification System (EDACS), this study aimed to determine its concurrent validity and reliability in children and adolescents with cerebral palsy (CP). Method After an extensive translation procedure, we applied the German language version to 52 participants with CP (30 males, 22 females, mean age 9y 7mo [SD 4y 2mo]). We correlated (Kendall's tau or Kτ) the EDACS levels with the Bogenhausener Dysphagiescore (BODS), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
3
25
0
4
Order By: Relevance
“…Like the other FCSs, EDACS has been shown to be valid and reliable for children and young people with CP 19 . Studies have demonstrated that EDACS meets quality standards for inter-observer reliability between health professionals, and between parents and health professionals 19,20,21,22 . High intra-rater-reliability 20 and strong construct validity 21,22 have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Like the other FCSs, EDACS has been shown to be valid and reliable for children and young people with CP 19 . Studies have demonstrated that EDACS meets quality standards for inter-observer reliability between health professionals, and between parents and health professionals 19,20,21,22 . High intra-rater-reliability 20 and strong construct validity 21,22 have also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for the sake of comparing results across time and place, we advise forming cohorts according to Gross Motor Function Classification System (GMFCS) [60] level or other commonly employed measures of gross motor functioning. For similar reasons, when possible, scales such as the Manual Ability Classification System (MACS) [61], the Communication Function Classification System (CFCS) [62], and the Eating and Drinking Ability Classification System (EDACS) [63] should be utilized. Other factors to account for can be gleaned from Section 4, perhaps chief among them gastrostomy status.…”
Section: External Validitymentioning
confidence: 99%
“…Having followed standard translation procedures, the authors demonstrate that the German version of the EDACS correlates moderate to high with other motor classification systems . This suggests that other systems measure different motor domains, such as ambulatory abilities, manual skills, or speech/language patterns.…”
mentioning
confidence: 95%
“…The Eating and Drinking Ability Classification System (EDACS) is a classification system in English designed to help communicate the eating and drinking ability of children with cerebral palsy . The study by Tschirren et al . focusses on this topic, though the language written and spoken in the geographic area of their study is German.…”
mentioning
confidence: 99%
See 1 more Smart Citation